Fabrication, characterization, and data analysis of 2D perovskite for LED application - Goh, Jun Jie (Nanyang Technological University, 2023)
This research investigates the degradation effects of 2D-organic inorganic halide perovskite (PEA)2PbBr4 in the working conditions of Perovskite Light-Emitting Diodes (PeLEDs) applications. Stability of (PEA)2PbBr4 is essential for the commercialization of PeLEDs to ensure the longevity of the device.